2013
DOI: 10.1007/s13402-013-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression and promoter methylation of the candidate biomarker TCF21 in head and neck squamous cell carcinoma

Abstract: Both over-expression and increased promoter methylation of TCF21 were frequently observed in HNSCCs. TCF21 promoter hypermethylation was found to lead to gene silencing in the HNSCCs, but not in the benign tonsils. These epigenetic, and possibly also genetic, alterations of the TCF21 gene in HNSCCs may be driven by HPV infection, nicotine and alcohol abuse, or both. These findings, together with its stage- and primary site-dependent expression, turn TCF21 into a promising candidate biomarker in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
“…28,33,34,44 In other publications studying overall HNSCC, OPSCC subgroup size ranged from 9% to 80% of the total study population. [29][30][31][32][35][36][37][38][39][40][41][42][43] There was only one study that reported the distribution of average age, nicotine and alcohol consumption between HPV-positive and HPV-negative tumors of which promoter methylation was evaluated. 34 The mean age in HPV-positive tumors was 56.9 compared with 58.4 in HPV-negative tumors.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations